Coaching Psychology: sebuah Pengantar - Teddi Prasetya Yuliawan (Faculty of Psychology Universitas Gadjah Mada, 2011)
Coaching is a rapidly growing realm in recent decades. More than just a popular field ofpsychology, coaching has also been the subject of discussion and research by psychologypractitioners and academics. This paper intends to provide an introduction to coaching psychology,a field that in the last 10 years has grown by psychology practitioners in Australia and Europe. Wediscuss the differences that coaching has compared to another field, the development of coachingpsychology, and the opportunity for future research and development. Hopefully, psychologypractitioners in this country will be interested to do research and development in this field, giventhe increasing interest, both from the psychology and non-psychology.